Pengaruh Permasalahan Peserta Didik terhadap Kualitas Pendidikan pada Sekolah Menenggah Atas - Sofiia Muntazza; Indah Wulandari; M.Rizki Hidayatullah; Sani Safittri; Syarifuddin Syarifuddin (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The problems faced by students have a considerable effect on the quality of education, particularly at the secondary education level. Internal factors such as academic stress, low learning motivation, and unstable psychological conditions can hinder students' academic development. Meanwhile, external factors such as family environment, complex curriculum, high education costs, and inadequate facilities further deteriorate the education system. These challenges contribute to low student achievement, increased dropout rates, and declining quality of social interactions in educational settings. This article uses a literature review approach to examine various. factors affecting education quality and explores possible solutions. The findings indicate that intervention from schools, parents, and the government is crucial to creating an inclusive, supportive, and responsive educational environment.